Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Get immediate answers to your questions from a wide network of experienced professionals on our Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Step-by-step explanation:
If F(x) = 2x+6, g(x) = 3² findf(g (-3))
Solution
f(g (-3)) = 2x+6(3²(-3)) = 2x+6(3×3(-3))
= 2x+6(-27) = 54x-162 = 54x = 162
54/54x = 162/54
x = 3
Answer:
➩ [tex]f(g(-3)) = 24[/tex]
Step-by-step explanation:
➨ Rearrange/Simplify the equations
[tex]F(x)=2x+6\\g(x)=9[/tex]
➨ Find [tex]f(g(-3))[/tex]
[tex]g(-3)=9[/tex] ➩ All x-values have same y-values ➩ Constant Function
Substitute [tex]g(-3) = 9[/tex] in the f(x)
[tex]f(g(-3)) = f(9)\\f(9)=2(9)+6\\f(9)=18+6\\f(9)=24\\f(g(-3)) = 24[/tex]
Thus, the answer ➩ [tex]f(g(-3)) = 24[/tex]
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.